Colonized bodies, worlds transformed : toward a global bioarchaeology of contact and colonialism - Murphy, Melissa Scott; Murphy, Melissa Scott; Klaus, Haagen D.; Klaus, Haagen D.; Larsen, Clark Spencer; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past, 2017)
Contact between separate human cultures have led to some significant adaptive transitions of humankind, particularly the collision between the Eastern and the Western Hemispheres beginning in A.D. 1492. Still, conquest and colonialism were not understood scientifically, long entwined with incomplete histories and assumptions regarding Native demographic collapse. Bioarchaeological studies of human remains have shed light on contact, including the realization that contact and colonialism were phenomenon not limited to the Columbian exchange. 'Colonized Bodies, Worlds Transformed' delves into bioarchaeology contact through new research of colonial encounters, culture contact, and colonialism from diverse areas.